2021
DOI: 10.1002/hep.31545
|View full text |Cite
|
Sign up to set email alerts
|

The Apelin–Apelin Receptor Axis Triggers Cholangiocyte Proliferation and Liver Fibrosis During Mouse Models of Cholestasis

Abstract: Background and Aims Apelin (APLN) is the endogenous ligand of its G protein–coupled receptor, apelin receptor (APJ). APLN serum levels are increased in human liver diseases. We evaluated whether the APLN–APJ axis regulates ductular reaction and liver fibrosis during cholestasis. Approach and Results We measured the expression of APLN and APJ and serum APLN levels in human primary sclerosing cholangitis (PSC) samples. Following bile duct ligation (BDL) or sham surgery, male wild‐type (WT) mice were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…PD98059 has been shown to inhibit ERK activities in vitro and in vivo 57,58 . Consistent with this, we found that PD98059 significantly reduced levels of pERK1/2 in Ppp2cα KO cortices and cultured 293 T cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PD98059 has been shown to inhibit ERK activities in vitro and in vivo 57,58 . Consistent with this, we found that PD98059 significantly reduced levels of pERK1/2 in Ppp2cα KO cortices and cultured 293 T cells.…”
Section: Discussionsupporting
confidence: 89%
“…26,46 PD98059 has been shown to inhibit ERK activities in vitro and in vivo. 57,58 Consistent with this, we found that PD98059 significantly reduced levels of pERK1/2 in Ppp2cα KO cortices and cultured 293 T cells. The observation of the decreased number of CC3+ cells inPD98059-treated Ppp2cα KO cortices suggests that PD98059 may be effective to inhibit apoptotic cell death in vivo.…”
Section: Discussionsupporting
confidence: 85%
“… n.a. 149 AG-012736 (Axitinib) Selective second-generation VEGFRs inhibitor Subcutaneous xenograft of human (NCC-BD1 and TKKK) CCA cell lines. Growth inhibition of NCC-BD1 and TKKK.…”
Section: Conclusion and Therapeutic Implicationsmentioning
confidence: 99%
“…In a study by Yasuzaki et al on rats, the ligand of Jo2, an apoptosis-associated antigen of Fas, was injected intraperitoneal, and it was observed that the expression of apelin and APJ were both increased, and serious apoptotic changes were detected in the liver in examinations performed after 3 and 6 h [ 58 ]. Another experimental mice study by Chen et al demonstrated that the apelin-APJ complex induced cholangiocyte proliferation and inflammation [ 59 ]. Melgar-Lesmes et al evaluated, in human liver cell cultures, hypoxia and inflammatory factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%